2016
DOI: 10.4103/2008-7802.178531
|View full text |Cite
|
Sign up to set email alerts
|

The effect of diabetes mellitus on apoptosis in hippocampus: Cellular and molecular aspects

Abstract: Background:Diabetes mellitus is associated with cognitive deficits in humans and animals. These deficits are paralleled by neurophysiological and structural changes in brain. In diabetic animals, impairments of spatial learning, memory, and cognition occur in association with distinct changes in hippocampus, a key brain area for many forms of learning and memory and are particularly sensitive to changes in glucose homeostasis. However, the multifactorial pathogenesis of diabetic encephalopathy is not yet compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 98 publications
(19 citation statements)
references
References 81 publications
(166 reference statements)
0
17
0
2
Order By: Relevance
“…In contrast, T2D patients display more consistently moderate cognitive impairments in verbal memory tasks and complex information processing. 40,[118][119][120] An increasing number of data and epidemiological studies also link diabetes and Alzheimer disease; 121,122 T2D being associated with an almost 2-fold increased risk of dementia. 123,124 By modifying the BBB physiology, diabetes/hyperglycemia could disturb the microenvironment of neural stem cell niches and impairs neural stem cell activity and newborn cell survival.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, T2D patients display more consistently moderate cognitive impairments in verbal memory tasks and complex information processing. 40,[118][119][120] An increasing number of data and epidemiological studies also link diabetes and Alzheimer disease; 121,122 T2D being associated with an almost 2-fold increased risk of dementia. 123,124 By modifying the BBB physiology, diabetes/hyperglycemia could disturb the microenvironment of neural stem cell niches and impairs neural stem cell activity and newborn cell survival.…”
Section: Resultsmentioning
confidence: 99%
“…37 STZ models of rat have shown that diabetes increases neuronal death through apoptotic mechanisms in the hippocampus. 40 For instance, the number of TUNEL-positive neurons was increased, [41][42][43] and the expression of pro-apoptotic protein such as Caspase-3 and Bax was upregulated. [44][45][46] Taken together, these data highlight that diabetes impairs neuronal survival by increasing Caspase-3 expression and activity, and apoptotic gene regulators 40 (Fig.…”
Section: Diabetes Impairs Brain Cell Survivalmentioning
confidence: 99%
“…The following mechanisms are recognized for memory and cognitive deficits in DM: (1) hyperglycemia is considered the most important cause of diabetes complications as well as memory and cognitive impairments [11, 50]; (2) diabetes causes apoptosis and neuronal loss in the hippocampus and the frontal cortex, which are associated with cognitive impairment [14, 15, 51, 52]; (3) oxidative stress associated with cognitive dysfunction in diabetes increases neuronal damage and death through protein oxidation, DNA damage, and peroxidation of membrane lipids [13, 14, 51, 52]; (4) cholinergic (as one of the most important neurotransmitter systems involved in learning and memory formation mechanisms) dysfunction in the brain of diabetic rats via the increased activity of acetylcholinesterase (the enzyme responsible for degrading acetylcholine and terminating its physiological action) and decreasing levels of cholineacetyltransferase (the enzyme responsible for acetylcholine synthesis) contributes to DM memory impairment [16, 53]; (5) microvascular function change is another pathophysiological reason for cognitive impairment in diabetes, which is attenuated by some antioxidant agents [11]; and (6) changes in energy metabolism, cerebral blood flow, and the blood-brain barrier also cause memory and cognitive impairments [16, 54, 55]. As stated before, decreasing hyperglycemia in the diabetic groups with CoQ10 treatment may account for restoration of memory and cognitive function in DM.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with long-standing diabetes commonly develop diabetic encephalopathy, which is characterized by cognitive decline 1 , neuronal apoptosis 2 , 3 , as well as neurochemical and structural abnormalities in the cortex and hippocampus 4 , 5 . Although the pathogenesis of diabetic encephalopathy is complex and not fully understood, methylglyoxal (MG) accumulation has been considered as one of the major contributing causes 6 , 7 .…”
Section: Introductionmentioning
confidence: 99%
“…The activated caspase-9, in turn, cleaves procaspase-3 to its active form, which induces cell apoptosis 18 . In the hippocampus of streptozotocin (STZ)-induced diabetic rats, Bax and caspase-3 mRNA or protein levels are considerably increased and related to impaired cognition as measured by the Morris water maze 3 . Therefore, neuronal apoptosis is likely to account for the concomitant emergence of cognitive impairments in the diabetic status.…”
Section: Introductionmentioning
confidence: 99%